Самовар с шампанским: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2015)
Экземпляры: ф.20 (20241029) / Инвентарный номер: 65306 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44